The volatile compound profile in the meat of chickens raised in a free-range system varies with sexual maturity - Joanna Oliveira Marçal; Giulia Piva Oliveira; Fernando Marcos Rubim; Laryssa Fernandes Correa; Diogo Batista dos Santos; Lais Gabrielle Alvarenga Assis; Adriano Geraldo; Peter Bitencourt Faria; Lidiany Mendon..a Zacaroni Lima (Food Chemistry Advances, 2022)
This study aimed to characterize and evaluate the profile of volatile compounds found in the meat of chickens raised in a free-range system as a function of their sex and sexual maturity. A completely randomized design (CRD) was used, and 90 birds were categorized as immature males, mature males, immature females or mature females. Samples of breast and drumstick cuts were analyzed. The volatile compounds were extracted by solid-phase microextraction (SPME), and the compounds were identified by mass spectrometry and the Kovats index. Ninety-six volatile compounds were identified. Aldehydes, terpenes, and alcohols composed the highest numbers of identified volatile compounds. There was a stronger relationship between aldehyde, ketone, terpene, furan and sulfur compounds with drumstick meat from mature males compared with the other samples. Ester compounds were more strongly associated with chicken meat from immature females in breast cut. In breast meat, the alcohol group was negatively correlated with immature chickens in both sexes and increased with sexual maturity. Compounds such as aldehydes, hydrocarbons, carboxylic acids, and pyrazines were more strongly related to the breast meat of mature females. There was a difference in the profile of volatile compounds between mature and immature chickens according to sex and cut. Male and female chickens demonstrated compounds that could change the taste of chicken meat, indicating that the influence of sexual maturity was a common factor.